(3eYGQL Gdage aj TQM GdfXes - (3GdMdis; (3GHf GdeWgQ GdMdj , LeGd GdOjf , CHh efUhQ,J (B726 (3g` s ((3GdfLa s)
(3ChdgG (B:s
(3GeG HYO aEfg deG habfG Gddg JYGdi ajeG Sda ef GdChbGa s
(3BNQgG (B:s
(3hOaY GdVQQ hGLH aGdJhHI hGLHI CeG GdeYUjI GdUZjQI aGhLH GdJhHI YfgG HGdSeY s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdadSaI hGdefWbs